Remidiasi Miskonsepsi Siswa Pada Materi Listrik Dinamis Menggunakan Ebook Interaktif - Mukhlis Hidayatulloh; Iskandar Wiryokusumo; Djoko Adi Walujo (Department of Physics Education, Universitas Mataram, 2019)
Based on previous research, the student had many misconceptions occurred in dynamic electrical material so the researcher developed interactive ebook of dynamic electrical material which was integrated with PhET simulation software to reduce misconception on that material. The purposes of this study are: (1) Describe the validity of an interactive ebook based on expert assessment in terms of material, media, and language and three physics teachers; (2) Describe the effectiveness of interactive ebook based on the decrease of student misconception after learning with developed ebook; and (3) Describe the practicality of the ebook based on the student response questionnaire. The method used in ebook development refers to the Instructional Design Strategy developed by Moore & Kearsley with the sequence: Analysis, Design, Development, Implementation, and Evaluations. The results of this study are: (1) Development of an interactive ebook is in a very decent category in terms of validity from expert assessment on material, media, and language ebook and three physics teachers; (2) The effectiveness of interactive ebook is in the effective category, it could reduce student misconceptions on dynamic electrical materials effectively; and (3) The developed ebook are very practical to use, responses of students were positively